INCREASING THE STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT THROUGH VISUAL SPATIAL INTELLIGENCE STRATEGY AT THE TENTH GRADE OF SMK NEGERI 2 GUNUNGSITOLI IN 2023/2024 - BUULOLO, GRACE NOVELIAN; MARU'AO, NURSAYANI; LAOLI, ADIELI; ZEBUA, ELWIN PIARAWAN (CENDEKIA: Jurnal Ilmu Pengetahuan, 2024)
Writing is the ability to communicate ideas, thoughts, and feelings to others through written language. Writing as a process that involves and teaches how to turn words, sentences, and paragraphs into good writing, as well as how to generate ideas and ways to interact with others, identify what they want to express, and try to understand it. Based on the explanation above, it can be concluded that writing is a process in which words and ideas are turned into phrases and paragraphs that are used to communicate with others and can speak and receive messages from the author through writing. The purpose of the research is to Increase the Students' Ability in Writing  Descriptive Text Through Visual Spatial Intelligence Strategy at Tenth Grade of SMK Negeri 2 Gunungsitoli Barat which the total numbers of the students was 20 persons. The research was conducted by using Classroom Action Research (CAR) design. This research was applied into two cycles. Each cycle consisted of planning, action, observation, and reflection. The instruments used by the researchers to collect the data were observation sheet, evaluation sheet and field note. In the second meeting of cycle II, the researchers obtained the improvement of students, who achieved the Minimum Competence Criterion (73). there were 11 (55%) students who got score among 85-100 classified as “Very Good Criteria”, 8 (40%) students got score among 75-84 classified as “Good Criteria”, 1 (4%) students  who got score among 60-74 classified as “Enough Criteria”,  no one  students who reached the “Less Criteria” and no one students who reached the “Very Less Criteria”. In Cycle II the average was 84, the highest mark was 96 and the lowest was 65. It implies that the students’ ability in write descriptive text increase in cycle II. ABSTRAKMenulis adalah kemampuan untuk mengkomunikasikan ide, pikiran, dan perasaan kepada orang lain melalui bahasa tulis. Menulis sebagai suatu proses yang melibatkan dan mengajarkan bagaimana mengubah kata, kalimat, dan paragraf menjadi tulisan yang baik, serta bagaimana menghasilkan ide dan cara berinteraksi dengan orang lain, mengidentifikasi apa yang ingin mereka ungkapkan, dan mencoba memahaminya. Berdasarkan penjelasan di atas, dapat disimpulkan bahwa menulis adalah suatu proses di mana kata-kata dan ide diubah menjadi frasa dan paragraf yang digunakan untuk berkomunikasi dengan orang lain dan dapat berbicara dan menerima pesan dari penulis melalui tulisan. Tujuan dari penelitian ini adalah untuk Meningkatkan Kemampuan Siswa dalam Menulis Teks Deskriptif Melalui Strategi Kecerdasan Visual Spasial di Kelas X SMK Negeri 2 Gunungsitoli Barat yang jumlah siswanya adalah 20 orang. Penelitian ini dilakukan dengan menggunakan desain Penelitian Tindakan Kelas (PTK). Penelitian ini diterapkan dalam dua siklus. Setiap siklus terdiri dari perencanaan, tindakan, observasi, dan refleksi. Instrumen yang digunakan oleh peneliti untuk mengumpulkan data adalah lembar observasi, lembar evaluasi dan catatan lapangan. Pada pertemuan kedua siklus II, peneliti memperoleh peningkatan siswa yang mencapai Kriteria Kompetensi Minimal (KKM) (73). Ada 11 (55%) siswa yang memperoleh nilai 85-100 yang tergolong “Kriteria Sangat Baik”, 8 (40%) siswa memperoleh nilai 75-84 yang tergolong “Kriteria Baik”, 1 (4%) siswa memperoleh nilai 60-74 yang tergolong “Kriteria Cukup”, tidak ada siswa yang mencapai “Kriteria Kurang” dan tidak ada siswa yang mencapai “Kriteria Sangat Kurang”. Pada Siklus II rata-ratanya adalah 84, nilai tertinggi adalah 96 dan terendah adalah 65. Ini menyiratkan bahwa kemampuan siswa dalam menulis teks deskripsi meningkat pada siklus II.